2006
DOI: 10.1002/hrm.20091
|View full text |Cite
|
Sign up to set email alerts
|

Family-friendly work practices in Britain: Availability and perceived accessibility

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(136 citation statements)
references
References 27 publications
6
124
3
1
Order By: Relevance
“…Despite some evidence that trade union membership can positively affect the availability of work-life balance programmes (Budd and Mumford, 2006) this study 25 showed that trade unions had no effect on work-life balance programmes. This may be due to the fact that only one third of hotels in the study were unionised (which reflects figures for the industry) and an interview with a trade union official reflected that more work needed to be done by unions to increase membership and to play a more active role in the workplace.…”
Section: Resultscontrasting
confidence: 74%
“…Despite some evidence that trade union membership can positively affect the availability of work-life balance programmes (Budd and Mumford, 2006) this study 25 showed that trade unions had no effect on work-life balance programmes. This may be due to the fact that only one third of hotels in the study were unionised (which reflects figures for the industry) and an interview with a trade union official reflected that more work needed to be done by unions to increase membership and to play a more active role in the workplace.…”
Section: Resultscontrasting
confidence: 74%
“…age and physical condition) (Geurs & Van Wee, 2004). Budd and Mumford (2006) found several flaws in the common generalization that high (area) accessibility equals high individual accessibility; meaning that objective generalizations do not take into consideration awareness of opportunities, ability to use, personal relevance or interest.…”
Section: Accessibilitymentioning
confidence: 99%
“…Up until now however, measuring accessibility has been limited to objective measures such as travel time or distance, not capturing the perceived accessibility of individuals or certain groups of people, limiting the usefulness of the link between accessibility and social inclusion since the measured accessibility may not capture the reality (Curl, Nelson, & Anable, 2011). This gap in measuring accessibility has been pointed out by researchers for years, urging for the inclusion of subjective accessibility (Budd & Mumford, 2006;Curl et al, 2011;Farrington, 2007;Handy & Niemeier, 1997;Stanley & VellaBrodrick, 2009;van Wee & Geurs, 2011), but up until now not much has been done. In 2015, we developed a quantifiable measurement for perceived accessibility in public transport, the Perceived Accessibility Scale (Lättman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, with the notable exceptions of Evans (2001) and 4/36 den Dulk (2005), current knowledge on the adoption of organizational work-life practices is restrained to a single-country context, mostly the United States. A limited set of factors have been found to impact the level and nature of the practices adopted: (1) Company size (Bond, Galinsky, Kim & Brownfield, 2005;den Dulk, 2005;Evans, 2001;Goodstein, 1994;Ingram & Simons, 1995;Tremblay, 2004), (2) industry (Goodstein, 1994;Ingram & Simons, 1995;Tremblay, 2004;Wood, de Menezes & Lasaosa, 2003), (3) geographical region (Friedman, 2001; Morgan & Milliken, 1992) (4) proportion of women in executive, management and professional positions (Bond & Galinsky, 1998;Ingram & Simons, 1995), (5) proportion of qualified workers or knowledge workers (Bond & Galinsky, 1998;Evans, 2001;Konrad & Mangel, 2000;Guérin, Saint-Onge, Haines, Trottier & Simard, 1997;Osterman, 1995) and (6) need to foster a high level of commitment (Budd et Mumford, 2006;Evans, 2001;Osterman,1995). Other determinants that are found in some studies but not others are publicsector and unionization (Dex & Scheibl 1999;Evans, 2001;Guérin & al.…”
Section: Introductionmentioning
confidence: 99%